2008
DOI: 10.1007/s00223-008-9187-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone Parameters are Improved with Intermittent Dosing of Vitamin D3 and Calcitonin

Abstract: Intermittent combination of an anabolic agent to promote bone formation and an antiresorptive agent that would prevent further bone loss is a theoretically attractive approach for restoring bone mass. We tested the potential of intermittently dosed calcitriol and calcitonin (CT) to restore bone properties in ovariectomized (Ovx) rats. Rats had Ovx or sham surgery at 8 weeks old and 4 weeks later were assigned to experimental groups: (1) sham vehicle, (2) Ovx vehicle, (3) Ovx + parathyroid hormone (PTH, 40 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In this experiment, the intermittent dosing of vitamin D 3 and calcitonin was adopted as a means to restore the detrimental effects of DM because these two hormones act on different cellular targets and could potentially have an additive beneficial effect. 9 Previous research work has shown that the administration of vitamin D 3 alone for prolonged periods or in high doses is not recommended due to the disturbances expected in calcemic activities; moreover, the application of calcitonin alone was found to be unable to restore detrimental effects on bone structure or mass caused by some systemic hormonal disturbances. 9 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this experiment, the intermittent dosing of vitamin D 3 and calcitonin was adopted as a means to restore the detrimental effects of DM because these two hormones act on different cellular targets and could potentially have an additive beneficial effect. 9 Previous research work has shown that the administration of vitamin D 3 alone for prolonged periods or in high doses is not recommended due to the disturbances expected in calcemic activities; moreover, the application of calcitonin alone was found to be unable to restore detrimental effects on bone structure or mass caused by some systemic hormonal disturbances. 9 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…The antiresorptive effect of calcitonin was previously suggested 9 , 10 , 21 , 29 and was considered safe and capable of stabilizing or increasing bone mineral density. In addition, calcitonin is a powerful inhibitor of osteoclast activity with only a transitory action because it is quickly eliminated from the skeleton, circulation and extravascular fluids, allowing normal remodelling to take place.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osteoblast activity is upregulated in the OVX rat [14, 3032]. At 4 weeks post-OVX, all dynamic histomorphometric measures (i.e., MS/BS, MAR, and BFR/BS) were significantly increased on the periosteal surface of the femoral diaphysis and in the trabecular region of the proximal tibial metaphysis in HCR and LCR OVX relative to sham animals (Fig.…”
Section: Discussionmentioning
confidence: 99%